1995
DOI: 10.1254/jjp.67.383
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Edema Induced by Angiotensin II in Rats

Abstract: ABSTRACT-Weperformed this study to demonstrate the experimental procedure for inducing pulmonary edema by angiotensin II (AT II) in rats and to determine the mechanism of hemodynamic pulmonary edema. In the pilot study, 10 pg/ml of AT II was found to be adequate as the edematogenic dose for inducing pulmonary edema. The edematogenic dose of AT II was intravenously given to rats pretreated with 20 mg/kg of an AT II-receptor antagonist, E 4177 (3-[(2"-carboxybiphenyl-4-yl)methyl]-2-cyclopropyl-7-methyl-3H-imidaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…If bilateral renal artery stenosis, or an abnormal contralateral kidney exists, this does not happen and volume overloading can be induced (2, 3), possibly leading to the increased cardiac afterload and APE. It was demonstrated that intravenous angiotensin II injection could produce APE in rats (8) and rabbits (9), possibly as a result of increasing cardiac afterload. However, patients with renovascular disease could experience ‘flash’ pulmonary edema without left ventricular dysfunction (4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…If bilateral renal artery stenosis, or an abnormal contralateral kidney exists, this does not happen and volume overloading can be induced (2, 3), possibly leading to the increased cardiac afterload and APE. It was demonstrated that intravenous angiotensin II injection could produce APE in rats (8) and rabbits (9), possibly as a result of increasing cardiac afterload. However, patients with renovascular disease could experience ‘flash’ pulmonary edema without left ventricular dysfunction (4, 5).…”
Section: Discussionmentioning
confidence: 99%
“…Edematogenous dose of AT-II is administered intravenously to rats. A 10 μg/ml solution of angiotensin II (AT-II) in saline pH 6–7 at 1 ml/kg is a sufficient edematogenous dose to induce pulmonary edema in rats [ 113 ].…”
Section: Methodology Of Literature Search and Selectionmentioning
confidence: 99%